Kontribusi E-Puskesmas dan Integrasi Layanan Primer (ILP) terhadap Internal Service Quality di Puskesmas Tebet - Awwalunisa Aprilia Wijaya; A Rohendi; Ign Wiseto P Agung (BADAN PENERBIT STIEPARI PRESS, 2025)
Low patient satisfaction at Tebel Health Center reflects the need to improve Internal Service Quality. Implementing e-Health Center and Primary Service Integration has the potential to be a solution, but its impact on ISQ has not been comprehensively measured. This study used a quantitative cross sectional design with a sample of 100 employees directly involved. Data were collected through structured questionnaires, semi structured interviews, and observations. Instrument validity was tested with item-total correlation and reliability with cronbach’s alpha, meanwhile data analysis used descriptive statistics multiple linear regression. The research resukts reveal that partially, e-Health Center has a significant positive effect on ISQ , ILP also has a significant positive effect on ISQ ,simultaneously, e-Healts and ILP have a significant effect on ISQ . The conclusion of this research reveal that e-Health and ILP proved to significantly improve ISQ.